Portal de consulta biblioteca virtual softnya s.a.s (2017)
Knowledge management should be treated, for the sake of accuracy, as management of internal and external organizational information for the generation of new goods that will influence the development of products and services with high added value, because knowledge can managed only as information, gathered, processed, organized, stored and disseminated through databases, shared information networks, virtual communities, among other means of data transfer and information.